GAMBARAN PATOLOGI PARU-PARU PADA ANJING LOKAL BALI YANG TERINFEKSI PENYAKIT DISTEMPER - Kardena, I Made; Winaya, IB Oka; Berata, I Ketut (Buletin Veteriner Udayana, 2012)
Canine distemper is a contagious disease, which can infect any dog species includingdomestic dog in Bali. This research used ten domestic dogs in Bali, which were naturallyinfected with canine distemper virus and have been positively confirmed by laboratory testusing RT-PCR method. Lung tissue changes have been identified on gross pathologicalobservation, i.e.: on average the lungs were changed in color and size. The lungs mainlychanged into pale or darker; in addition, the lungs tended to become bigger. Mean while,the septa alveoli of the lungs observed thicker and were infiltrated by inflammatory cells.This tissue changes indicated that canine distemper virus which infected domestic dog inBali caused inflammatory reaction in lung, which is known as interstitial pneumoniainterstitial. These changes implied to be related to the disturbance of the respiration tract,which was accompanied by mucus-purulent exudates
Keywords: lung pathology, domestic dog, canine distemper